Assessing the energy intensity of alternative chemical and cryogenic natural gas purification processes in LNG production. (20th January 2019) - Rocco, Matteo V.; Langè, Stefano; Pigoli, Lorenzo; Colombo, Emanuela; Pellegrini, Laura A.
Abstract: The production of Liquefied Natural Gas (LNG) from natural gas reservoirs with high content of acidic compounds is expected to be a strategic and crucial issue for the development of the natural gas market in future decades. Therefore, the identification of alternative suitable processes for the synergistic natural gas purification and LNG production, when the amount of CO2 in the raw gas feed is high, and their comparative thermodynamic assessment, is necessary to foster a cleaner and efficient production of LNG. In this paper, the energy intensity of the classical chemical absorption units using aqueous solutions of Methyldiethanolamine (MDEA) and the novel Dual Pressure Low-Temperature Distillation process (DPD) operating in different national contexts is assessed by means of the Net Equivalent Methane analysis and the Energy Life Cycle Assessment. These methods return respectively the equivalent methane and the embodied non-renewable energy invoked by the two alternative processes in one operating year. In general, the primary energy required by the construction phases of both the systems results negligible compared to the operation phase, and most of the latter is due to the consumption of energy utilities, which is strongly dependent by the considered national context. According to the results obtained by means of both the methodologies, the DPD process is generally less energy intensive compared to MDEA: the DPD process results to be an efficient and promising technique to perform the synergistic natural gas purification and LNG production. Highlights: Exploitation of acidic natural gas reserves and LNG production will play key role in future decades. Two alternative processes for acid natural gas purification and LNG production are introduced. Net Equivalent Methane method and Energy LCA of the processes are comparatively applied. Both the methods confirm that Dual Pressure Low-Temperature Distillation has the lowest energy intensity.